Cumulative learning and sustained engagement in an introduction to accounting course. Issue 1 (5th February 2018) - Aldamen, Husam; Duncan, Keith; Ziegelmayer, Jennifer L.
Abstract : Purpose: Due to its technical focus, the introductory accounting course has a hierarchical knowledge structure that requires students to master and integrate abstract knowledge which builds on itself over time. The purpose of this paper is to explore the relationship between engagement and examination performance for students enrolled in a hierarchically structured course. Design/methodology/approach: This research involves a retrospective study of an introduction to accounting course examining the relationship between increased engagement and examination performance. Students are provided opportunities for engagement through assigned homework and optional ungraded assignments. Performance is measured by scores on each of three examinations conducted throughout the semester. Findings: The study finds that additional engagement in assignments has no significant impact on mid-semester examination performance; however, sustained engagement throughout the semester has a cumulative impact on final examination performance. Moreover, students that perform well on mid-semester examinations do not benefit from additional engagement, whereas students that perform poorly on the mid-semester examinations exhibit substantially higher final examination scores from sustained engagement. Practical implications: This study illustrates the complex interplay between engagement and performance and the timing of performance gains. The implication for educators is that increased sustained engagement is likely to result in increased but delayed student performance gains in disciplines with hierarchical knowledge structures. Originality/value: This study contributes to the literature in its examination of the timing of performance benefits gained from increased engagement in courses with a cumulative knowledge base.